Ab Initio Calculations for the Electronic, Interfacial and Optical Properties of Two-Dimensional AlN/Zr2CO2 Heterostructure - Ren, Kai; Zheng, Ruxin; Lou, Junbin; Yu, Jin; Sun, Qingyun; Li, Jianping (Frontiers in Chemistry, 2021)
Recently, expanding the applications of two-dimensional (2D) materials by constructing van der Waals (vdW) heterostructures has become very popular. In this work, the structural, electronic and optical absorption performances of the heterostructure based on AlN and Zr2CO2 monolayers are studied by first-principles simulation. It is found that AlN/Zr2CO2 heterostructure is a semiconductor with a band gap of 1.790 eV. In the meanwhile, a type-I band structure is constructed in AlN/Zr2CO2 heterostructure, which can provide a potential application of light emitting devices. The electron transfer between AlN and Zr2CO2 monolayer is calculated as 0.1603 |e| in the heterostructure, and the potential of AlN/Zr2CO2 heterostructure decreased by 0.663 eV from AlN layer to Zr2CO2 layer. Beisdes, the AlN/Zr2CO2 vdW heterostructure possesses excellent light absorption ability of in visible light region. Our research provides a theoretical guidance for the designing of advanced functional heterostructures.